The complete chloroplast genome sequence of Myricaria wardii Marquand 1929 (Tamaricaceae): a shrub species endemic to the Tibet Plateau - Haoran Liu; Godfrey Kinyori Wagutu; Yuanyuan Chen; Xiuling Li; Xiangrong Fan (Mitochondrial DNA. Part B. Resources, 2024)
AbstractMyricaria wardii Marquand 1929, endemic to the Tibet Plateau, is a perennial shrub with important medicinal and ecological values. In this study, the complete chloroplast (cp) genome of M. wardii was assembled, and the phylogenetic tree was reconstructed to evaluate the phylogenetic location of the species. The results showed that the cp genome size of the M. wardii was 155,299 bp, which contained a pair of inverted repeat (IR) regions (26,150 bp), a large single copy (LSC) region (84,715 bp), and a small single copy (SSC) region (18,284 bp). The total GC content of the cp genome was 36.30%. A total of 128 genes were annotated, consisting of 83 protein-coding genes, 37 tRNA genes and 8 rRNA genes. The phylogenetic analysis showed that M. wardii was closely related to M. prostrata. This study provides useful information for the conservation of this species and the phylogenetic analysis of Tamaricaceae.